Digitalisasi sebagai Titik Balik Ekonomi Kerakyatan: Transformasi, Tantangan, dan Masa Depan UMKM Indonesia - Indah Damayanti; Kiromim Baroroh; Isroah Isroah (Pusat Riset dan Inovasi Nasional, 2026)
This paper examines the shift in the economic paradigm in Indonesia through digitalization, driven by the Fourth Industrial Revolution and the transition towards Society 5.0. The people's economy based on SMEs faces significant new challenges and opportunities in this era. Using a literature approach and case studies, this article highlights how information technology plays a role not only as a marketing tool but also as an instrument to strengthen economic sovereignty in accordance with the mandate of Article 33 of the 1945 Constitution. The findings indicate that the success of digital transformation depends on the synergy between supportive government policies, private sector innovation, and the adaptability of SME actors. In facing global challenges, the proposed strategy includes strengthening digital literacy for all levels of society and protecting the domestic market from the influx of foreign products that could threaten the sustainability of SMEs. This is crucial to ensure the future resilience of the national economy while also promoting the sustainable growth of the SME sector. Thus, digitalization is not only an efficiency solution but also a key factor in reinforcing Indonesia's people-based economy in the globalization era.